Does optical coherence tomography identify arterial healing after stenting? An in vivo comparison with histology, in a rabbit carotid model. Issue 2 (16th July 2007) - Prati, F; Zimarino, M; Stabile, E; Pizzicannella, G; Fouad, T; Rabozzi, R; Filippini, A; Pizzicannella, J; Cera, M; De Caterina, R
Abstract : Objective: To verify whether optical coherence tomography (OCT) can accurately monitor the occurrence of arterial healing after stenting. Setting: Delayed stent endothelialisation may predispose to stent thrombosis. OCT is a high-resolution intravascular imaging technique that accurately identifies stent struts and arterial tissues. Design and interventions: Eight New Zealand white rabbits underwent the implantation of single bare metal stents (diameter 2–2.5 mm, length 8–13 mm) in the right common carotid artery through the external carotid artery. After a median of 11 days (range 2–28), the stented arteries were visualised by OCT, with images acquired at a pull-back speed of 0.5 mm/sec. The rabbits were then euthanised, vessels were formalin-fixed and finally processed for histopathology. Results: We analysed 32 cross-sections from eight stented carotid arteries, for a total of 384 stent struts. OCT detected all of the stent struts in 30 of 32 cross-sections (93.7%), and correctly identified the presence/absence of tissue for every strut. Histological and OCT measurements of mean neointima thickness (0.135 (SD 0.079) mm and 0.145 (SD 0.085) mm, respectively, p = NS) were similar and closely related (r = 0.85, p<0.001). Neointima area progressively increased with longer time intervals from stent deployment to sacrifice; histological and OCT measurements were similar for each time interval. The intra-observer and interobserver reproducibility of OCT neointima measurements were excellent (R2 = 0.90 and 0.88, respectively). Conclusions: OCT is a promising means for monitoring stent strut coverage and vessel wall healing in vivo, the relevance of which will become even more significant with the increasing use of drug-eluting stents.